Performance Improvement Model for Cooperatives Through Reputation, Innovation, Cultural Transformation, and Competitive Advantage - Sobar, Agus; Aziz, Yudi; Mombang, Mombang; Darmansyah, Darmansyah (Majalah Ilmiah Bijak, 2025)
This study aims to analyze the influence of reputation, innovation, cultural transformation, and competitive advantage on improving the performance of cooperatives in West Java Province. Using the Resource-Based View (RBV) theory approach, this study positions reputation, innovation, and cultural transformation as strategic resources that can drive competitive advantage and enhance cooperative performance. The research methodology employs a quantitative approach with Structural Equation Modeling (SEM). Data were collected through surveys distributed to cooperative managers and members in West Java. The variables measured include organizational reputation, innovation levels, cultural transformation implementation, competitive advantage, and cooperative performance. The findings reveal that reputation has a significant impact on innovation and cultural transformation. Innovation has been proven to enhance the competitive advantage of cooperatives, while cultural transformation strengthens the relationship between reputation and organizational performance. Competitive advantage serves as an important mediator in improving the overall performance of cooperatives. The practical implications of this study underscore the necessity for cooperatives to strengthen their reputation through transparency and openness, promote innovation based on member needs, and adopt adaptive work cultures in response to change. Governments and stakeholders are also expected to provide strategic support through policies that foster cooperative development as a pillar of community economic empowerment.